(untitled) (Applied Biological Research, 2023)
In this study we compared the cytotoxic properties of several dental materials on cell cultures. Six products chosen for the study were alginate impression material, zinc phosphate cement, tissue conditioner for temporary denture soft relining, acrylic temporary crown and bridge material, heat curing acrylic resin and acrylic teeth. The samples were tested forcytotoxic properties by MTT test on Vero CCL-81 (ATCC) cell line. The most cytotoxic potential was observed for zincphosphate cement sample (cell survival, 5%) and highest biocompatibility for thermally polymerized acrylic resin (>70%). On exposure of dental materials to cytotoxic properties it did not completely cross out the product, being developed as a Medical Device. However, it requires further appropriate testing.